Pengaruh Work-Life Balance dan Job Burnout Terhadap Produktivitas Kerja Karyawan (Studi Pada PT BTN KC Medan) - Br Sinuhaji, Desy Sabriana; Simanjorang, Feronica (Universitas Serambi Mekkah, 2024)
The HR function is critical to achieving business goals. Maintaining a good and friendly working relationship between employees and all other aspects of HR is very important for HR management to achieve satisfactory employee performance and achieve a very high level of work efficiency. This study aims to analyze how work-life balance and job burnout affect work productivity at PT BTN Medan Branch Office. The research method used is quantitative with an associative approach and sampling using probability sampling method with simple random sampling. The population amounted to 155 people and 61 respondents were sampled. The results showed that the work-life balance variable (X1) had an effect on work productivity (Y). Meanwhile, it is known that the job burnout variable (X2) has no effect on work productivity (Y), but the work-life balance and job burnout variables simultaneously affect work productivity.